Sunflower oil methanolisys and glycerol ketalisation: Stepwise production of biofuels and additives with 3-methylimidazolium hydrogensulphate as catalyst - Barbosa, Sandro L.; Barbosa, Bruna K.; Lima, Camila D.; MacEdo, Alice L.; Mendonca, Jacqueline N.; Glososki, Giuliano C.; Lopes, Norberto P.; Klein, Stanlei I. [UNESP] (My University, 2016)
The ionic liquid 3-methylimidazolium hydrogensulfate is soluble within the glycerol phase that it creates, after catalyzing the transesterification of sunflower oil to fatty acids methyl esters with methanol. Separation of this phase and addition of acetone allow the production of the 5-membered ketal 2,2-dimethyl-1,3-dioxylane-4-yl-methanol, in which the catalyst is insoluble and is removed by decantation. After drying under vacuum, the ionic liquid is ready to rerun to the two-stage cycle with no apparent loss of activity.
Keywords: Biodiesel additive; Glycerol; Ionic liquid; Ketal production; Sunflower oil; Transesterification